THE QUARKS of OBJECT-ORIENTED DEVELOPMENT. - Armstrong, Deborah J. (Communications of the ACM, 2006)
The article describes the fundamental concepts, or quarks, of object-oriented (OO) development, and identifies how these concepts fit together into a coherent scheme. This analysis consisted of reviewing each source document for the identification of specific concepts (quarks) as the OO concepts and fitting them into a sampling frame. An object is an individual identifiable item which contains data about itself and descriptions of its manipulations of the data. A class is a description of the organization and actions shared by one or more similar objects. Encapsulation is a technique for desiring classes and objects that restricts access to the data and behavior by defining a limited set of messages that an object of that class can receive.